Factors influencing job performance among private sector employees in Klang Valley - Nur Athirah, Tarmizy (2024)
Work performance is very important in managing work in an organization so that organizational productivity can be increased. Through this, it is very important the work performance in the whole organization. This can also affect the economic growth of a country. Therefore, it is important to identify factors that affect work performance. Among the factors that affect work performance are mental health well-being, social support at work and a good work environment. Therefore, the main objective of this study is to identify the relationship of mental health well-being, social support at work, and environment at work-on-work performance. Data collected using a random online survey form around the Klang Valley, namely in the state of Selangor and the Kuala Lumpur metropolitan area. The survey form was randomly distributed to 384 respondents, but only 335 respondents in private companies in the Klang Valley who worked as nonmanagement employees responded. The results found that all factors contribute to work performance.